2017
DOI: 10.1051/0004-6361/201730839
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a helical prominence in 3D from IRIS spectra and images

Abstract: Context. Movies of prominences obtained by space instruments e.g. the Solar Optical Telescope (SOT) aboard the Hinode satellite and the Interface Region Imaging Spectrograph (IRIS) with high temporal and spatial resolution revealed the tremendous dynamical nature of prominences. Knots of plasma belonging to prominences appear to travel along both vertical and horizontal thread-like loops, with highly dynamical nature. Aims. The aim of the paper is to reconstruct the 3D shape of a helical prominence observed ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
2
21
2
Order By: Relevance
“…Schmieder et al (2014a) confirmed the horizontality for the magnetic field in prominences from a resolved He i D 3 observation interpreted with a principal component analysis (PCA) applied to the polarization profiles (López Ariste & Casini 2002Casini et al 2003Casini et al , 2005Casini et al , 2009. Further investigations were possible inside the fine structure of the prominences with a better spatial resolution (Levens et al 2016a(Levens et al ,b, 2017Schmieder et al 2017).…”
Section: Horizontality Of the Magnetic Field In A Prominencesupporting
confidence: 56%
“…Schmieder et al (2014a) confirmed the horizontality for the magnetic field in prominences from a resolved He i D 3 observation interpreted with a principal component analysis (PCA) applied to the polarization profiles (López Ariste & Casini 2002Casini et al 2003Casini et al , 2005Casini et al , 2009. Further investigations were possible inside the fine structure of the prominences with a better spatial resolution (Levens et al 2016a(Levens et al ,b, 2017Schmieder et al 2017).…”
Section: Horizontality Of the Magnetic Field In A Prominencesupporting
confidence: 56%
“…The IRIS movie of Mg II slit-jaws suggests instead more that this flow could correspond to a counter-streaming flow along large loops, changing direction with time (Zirker et al 1998). We should be able to reconstruct the horns in 3D using the slit jaw images and the spectra of IRIS obtained simultaneously to understand the nature of this horn-like structure (Schmieder et al 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…If we assume that the cool material moves along the magnetic field lines in prominences, the velocity vectors then mimic the magnetic field configuration. For one helical prominence observed with Hinode/SOT and IRIS it was possible to follow small knots along magnetic loops in the plane of the sky and derive the transverse velocity field, which combined with the Dopplershifts allows us to derive the velocity vectors (Schmieder et al 2017b). The Mg II line spectra and slit jaw images were used for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Filaments can be optically thick at EUV wavelengths (Anzer & Heinzel 2005) and therefore are typically observed in the chromospheric lines (see e.g. Schmieder et al 2017;Zapiór et al 2019). Numerical models revealed that filaments are located in magnetic dips within large flux ropes composed of twisted field lines (see e.g.…”
Section: Introductionmentioning
confidence: 99%